Mengatasi Kekurangan Kasih Sayang di Panti Asuhan Hanifa III Kampuang - Melani Melani; Fadhilla Yusri (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
Orphanages play an important role in helping children get protection, education and care for children who have lost their parents or been separated from their parents. One of the main challenges faced by these orphanages is love, which can have a serious impact on children's development. With this research, we used a qualitative descriptive approach to understand, describe and analyze the problem of lack of compassion at the Hanifa III Kampuang Orphanage. The results of this research will reveal that a lack of affection can cause children to feel lonely, anxious, and have difficulty forming healthy social relationships. The important role of administrators and social workers in providing compassion should not be overlooked. To overcome this problem of lack of love, the solution is to increase the number of administrators, provide training to them about the importance of compassion and invite the community to participate to help support the orphanage.